2022
DOI: 10.1002/anse.202200017
|View full text |Cite
|
Sign up to set email alerts
|

LC–MS Reveals Isomeric Inhibition of Proteolysis by Lysosomal Cathepsins

Abstract: Defects in autophagy are implicated in many age‐related diseases that cause neurodegeneration including both Alzheimer's and Parkinson's. Within autophagy, the lysosome plays a crucial role by enabling the breakdown and recycling of a wide range of biomolecular species. Herein, the effects of isomerization of aspartic acid (Asp) on substrate recognition and degradation are investigated for a collection of lysosomal cathepsins using liquid chromatography coupled to mass spectrometry. By examining a series of sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Similarly, peptide neurotransmitters and toxins have been found to contain d -amino acids which increase lifetimes by conferring resistance to proteolysis. , In terms of LLPs, isomerization can potentially disrupt proteostasis by preventing the breakdown into constituent amino acids. For example, studies of the lysosomal cathepsins have shown that isomerized substrates cannot be fully digested, which could eventually lead to lysosomal storage observed in Alzheimer′s disease (AD). , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, peptide neurotransmitters and toxins have been found to contain d -amino acids which increase lifetimes by conferring resistance to proteolysis. , In terms of LLPs, isomerization can potentially disrupt proteostasis by preventing the breakdown into constituent amino acids. For example, studies of the lysosomal cathepsins have shown that isomerized substrates cannot be fully digested, which could eventually lead to lysosomal storage observed in Alzheimer′s disease (AD). , …”
Section: Introductionmentioning
confidence: 99%
“…For example, studies of the lysosomal cathepsins have shown that isomerized substrates cannot be fully digested, which could eventually lead to lysosomal storage observed in Alzheimer′s disease (AD). 15,16 Although the lysosome appears to be unable to degrade isomerized substrates, the ubiquitin−proteasome system is another possible pathway for protein degradation. Within the mammalian cell, the 26S proteasome is a major complex composed of a core 20S unit responsible for enzymatic digestion and one to two outer 19S regulatory units that act together for the digestion and recycling of protein/peptide substrates.…”
Section: ■ Introductionmentioning
confidence: 99%